Pengumuman Laba Kuartalan dan Respon Investor saat Pandemi Covid-19 di Indonesia: Sebuah Studi Peristiwa - Novi Amelia; Yurniwati Yurniwati; Rahmat Febrianto (Universitas Batanghari Jambi, 2022)
This research aims to examine and prove empirically the effect of the announcement of quarterly earnings information during the Covid-19 pandemic on investor responses by using event studies. The dependent variable in this study is the investor's response as measured by cumulative abnormal return (CAR). The observation window used in this study was 7 days, namely three days before the announcement and three days after the announcement. The independent variable is the announcement of quarterly earnings as measured by unexpected earnings (EU). This study also examines the effect of changes in quarterly income, type of industry, and growth in Covid-19 cases as control variables on investor response. The sample in this study was 2,212 which were determined using the purposive sampling method. The results of the study prove that the announcement of quarterly earnings has a statistically significant effect on investor responses in several windows, changes in revenue have no effect on investor responses for all windows used, only in the windows t0;t2 CAR for financial and non-financial companies is different and significant. statistically, and the growth of covid cases was influential and statistically significant for several windows.